Nanomaterial assisted diagnosis of dopamine to determine attention deficit hyperactivity disorder - 'An issue with Chinese children'. (July 2022) - Xing, Jie; Zhang, Yong; Xu, Shuying; Zeng, Xiangping
Highlights: Attention deficit hyperactivity disorder (ADHD) is associated with dopamine. 'Biosensors' proposed, nanomaterial & biomolecule assisted dopamine sensing. Video games such as 'Sand-box', helps to minimize the consequences of ADHD. Nanomaterials used as, nanofilm, nanoparticle, nanopowder and nanohybrid. Gleaned sensing strategies for dopamine biosensors to fulfil necessities for ADHD. Abstract: Parkinson's and Alzheimer's diseases, schizophrenia, and attention deficit hyperactivity disorder (ADHD) are associated with mental or psychological disorder at differential expressions of dopamine. Among these, ADHD is highly related with the habit to focus on video games such as 'Sand-box', which helps to minimize the consequences of ADHD. A growing progression with sand-box players especially with Chinese Children brought a step ahead with the healthcare and creativity. Since dopamine changes are highly correlated to ADHD, several diagnostics as 'biosensors' have been proposed and demonstrated well in several instances. Further, nanomaterial and biomolecule assisted dopamine sensors have promoted the sensing systems to higher levels due to the minute detection. Nanomaterials have been used in different formats such as, nanofilm, nanoparticle, nanopowder, nanohybrid and with similar formats. Current overview gleaned various sensing strategies with dopamine biosensors to fulfil the necessities for ADHD and other disorders towards minimizing the growing number of cases especially with young generation.